Preparation method and device of honeycomb CO oxidation catalyst with simplified process

Through the process-simplified preparation method of cellular CO oxidation catalyst, the problems of low utilization rate of raw materials, unstable performance and poor adaptability to environmental changes in the prior art are solved, and the high activity, stability and adaptability are greatly improved.

CN119524866APending Publication Date: 2025-02-28BEIJING FUSION ENVIRONMENTAL PROTECTION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411417343.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing CO oxidation catalyst preparation process has problems such as low raw material utilization, unstable catalyst performance and poor adaptability to environmental changes.

Method used

The process-simplified honeycomb CO oxidation catalyst preparation method is adopted to form a catalyst with high specific surface area, uniform distribution of active components and enhanced adhesion through steps such as raw material mixing, sol preparation, gelation, drying, primary calcining, pretreatment, secondary calcining, impregnation, heat treatment, post-treatment, performance testing, aging treatment and packaging.

Benefits of technology

It improves the active sites and stability of the catalyst, simplifies the preparation process, enhances the adaptability to environmental changes, and improves catalytic activity and long-term stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524866A_ABST
    Figure CN119524866A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and device of a honeycomb CO oxidation catalyst with a simplified process, and belongs to the field of catalyst preparation, and the preparation method comprises the following steps: (1) raw material mixing: weighing TiO2, CeO2, ZrO2, Fe2O3, Nb2O5, CaO and SiO2 raw materials according to a ratio, and mixing with deionized water to form a basic composition of the catalyst; (2) sol preparation: mixing the basic composition with a stabilizer to form uniform sol; (3) gelation: aging the sol to form gel; (4) drying: drying the gel at 60-80 DEG C to form dry gel; and (5) primary calcination: calcining the xerogel at 500-800 DEG C to form a primary catalyst structure and the like. The catalyst has the advantages that the raw materials are diversified, a composite carrier is formed by mixing multiple raw materials, and the active sites and the stability of the catalyst are increased. And the whole preparation process is clear in steps, simple and convenient to operate and easy to realize industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a honeycomb CO oxidation catalyst with a simplified process and a device thereof, belonging to the field of catalysts. Background Art

[0002] The existing CO oxidation catalyst preparation process has some limitations, especially in terms of raw material utilization, catalyst performance stability and adaptability to environmental changes. The following is an expanded discussion of these issues:

[0003] Low raw material utilization: In the traditional CO oxidation catalyst preparation process, raw materials are often not completely converted into target products, resulting in raw material waste and increased costs. For example, precious metals such as platinum and palladium may be used in the preparation process, but the utilization rate of these precious metals is not high, and some raw materials are lost as waste during the preparation process.

[0004] The sintering flue gas has complex components and many types of impurities, which can easily lead to CO catalyst poisoning and deactivation at a fast rate.

[0005] Poor adaptability to environmental changes. Under different operating conditions, such as changes in temperature, pressure, and humidity, the performance of the catalyst may drop significantly. For example, some catalysts are not active enough under low temperature conditions, but are prone to thermal deactivation under high temperature conditions. Summary of the invention

[0006] In order to overcome the defects of the prior art, the present invention provides a method for preparing a honeycomb CO oxidation catalyst with a simplified process. The technical solution of the present invention is:

[0007] A preparation method of a honeycomb CO oxidation catalyst with a simplified process, characterized in that it comprises the following steps:

[0008] (1) Raw material mixing: TiO2, CeO2, ZrO2, Fe2O3, Nb2O5, CaO and SiO2 are weighed according to the ratio and mixed with deionized water to form the basic composition of the catalyst;

[0009] (2) Sol preparation: mixing the base composition with the stabilizer to form a uniform sol;

[0010] (3) Gelation: Aging the sol to form a gel;

[0011] (4) Drying: Drying the gel at 60-80°C to form a xerogel;

[0012] (5) Initial calcination: calcining the dry gel at 500-800 °C to form a preliminary catalyst structure;

[0013] (6) Pretreatment: The catalyst structure after the initial calcination is pretreated to form a carrier, and the pretreatment includes washing and acid washing steps to enhance the adhesion of the active components;

[0014] (7) Secondary calcination: The pretreated support is subjected to secondary calcination to ensure the cleanliness of the support surface and the uniform distribution of the active components;

[0015] (8) Impregnation: Impregnating the secondary calcined support in an impregnation solution, wherein the concentration of the impregnation solution is controlled at 0.5 to 10 wt % and the impregnation time is controlled at 0.5 to 2 h;

[0016] (9) Heat treatment: The impregnated support is heat treated in an inert gas atmosphere at a temperature of 200-500° C. for a time of 2-12 hours;

[0017] (10) Post-processing: cutting, grinding and cleaning the heat-treated carrier;

[0018] (11) Performance testing: The catalyst obtained by post-treatment is subjected to performance testing, including specific surface area, porosity, dispersion of active components and catalytic activity evaluation;

[0019] (12) Aging treatment: The catalyst is aged under conditions simulating actual operating conditions to evaluate its long-term stability and durability;

[0020] (13) Packaging: Packaging the catalyst that has undergone performance testing and aging treatment;

[0021] The step (1) is specifically as follows: the weight parts of the components of the raw materials are as follows: TiO2 60-75 parts; CeO2 15-25 parts; ZrO2 5-10 parts; Fe2O3 5-10 parts; Nb2O5 3-6 parts; SiO2 5-10 parts; CaO 1-3 parts, wherein the total amount of deionized water is 30% to 40% of the total weight of the raw materials.

[0022] The step (2) is specifically as follows: the stabilizer is polyvinyl alcohol or polyacrylic acid to prevent the particles in the sol from agglomerating and maintain the uniformity of the sol; the mass ratio of the stabilizer to the basic component is 1:0.1-1:0.5.

[0023] In the step (3), the sol aging temperature is controlled at 20-40° C., and the aging time is 2-24 hours.

[0024] In the step (6), the pickling step is specifically as follows:

[0025] Select dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid as the pickling solution, and the concentration of the pickling solution is between 1% and 10%; the temperature of the pickling process is controlled between room temperature and 60°C to ensure the pickling effect and reduce corrosion to the catalyst; the pickling time is usually 30 minutes to 2 hours; after pickling, use deionized water to rinse the catalyst to neutralize the residual acid solution and ensure that the catalyst surface reaches neutrality; in the step (7), the temperature range of the secondary calcination is between 400°C and 800°C, and the calcination time is 3-15 hours.

[0026] The step (11) is specifically as follows:

[0027] First, the catalyst samples were degassed to remove the gas adsorbed on the surface;

[0028] Then, the sample was cooled to liquid nitrogen temperature, nitrogen was gradually injected into the sample, and the adsorption amount was measured;

[0029] The specific surface area A was calculated using the BET equation:

[0030] Among them, V 吸附 is the adsorption volume, NA is Avogadro's constant, R is the gas constant, P0 is the saturated vapor pressure, C is the adsorbate-adsorbent interaction constant, P is the equilibrium pressure, and θ is the coverage of the adsorbed gas;

[0031] The pore volume and pore size distribution were determined by nitrogen adsorption method and calculated by the following formula: V 孔 is the pore volume, V 催化剂 is the total volume of the catalyst;

[0032] Active component dispersion test: X-ray diffraction and transmission electron microscopy were used to observe the crystal structure of the catalyst and the distribution of active components;

[0033] The metal dispersion D is calculated by the following formula:

[0034] Among them, A 金属 is the surface area of ​​the metal component, A 总 is the total surface area of ​​the catalyst;

[0035] The catalytic activity was evaluated by the turnover frequency:

[0036] Conversion frequency = reaction rate / number of active sites, where the reaction rate is expressed in moles per second and the number of active sites is determined by X-ray photoelectron spectroscopy.

[0037] The step (12) is specifically as follows:

[0038] Aging condition setting: set the temperature, humidity, and gas flow parameters for the aging process; Temperature control: use the PID control algorithm to accurately control the temperature of the aging process. The output of the PID controller can be calculated using the following formula:

[0039] Kp is the proportional gain, Ki is the integral gain, K d is the differential gain, e(t) is the deviation, i.e. the difference between the desired temperature and the actual temperature, and dt is the time interval;

[0040] Humidity control: The humidity in the aging environment is controlled by adjusting the flow and concentration of water vapor. Humidity control is monitored and adjusted by the following formula:

[0041] H = W / P × 100% where W is the partial pressure of water vapor and P is the saturated partial pressure of water vapor;

[0042] Gas flow control: Use a mass flow controller to control the gas flow. The gas flow Q is calculated by the following formula: Q = V / t, where V is volume and t is time;

[0043] Aging time: The aging time is estimated by the following formula: T = T0 × e (-k·ΔH) ; Where T0 is the initial time, k is the rate constant, and ΔH is the activation energy of the aging reaction.

[0044] A device for implementing the method for preparing a honeycomb CO oxidation catalyst with a simplified process, comprising:

[0045] A raw material mixing unit, used for mixing raw materials;

[0046] A sol preparation unit, used for mixing the basic composition with the stabilizer to form a uniform sol;

[0047] A gel forming unit, used for aging the sol to form a gel;

[0048] A drying unit, used for drying the gel to form a xerogel;

[0049] The primary calcination unit is used to calcine the dry gel to form a preliminary catalyst structure; the pretreatment unit is used to pretreat the catalyst structure after the primary calcination to form a carrier;

[0050] A secondary calcination unit, used for secondary calcining the pretreated carrier;

[0051] An impregnation unit, used for impregnating the secondary calcined support into an impregnation liquid;

[0052] A heat treatment unit is used to heat treat the impregnated carrier in an inert gas atmosphere; a post-treatment unit is used to perform post-treatment steps of cutting, grinding and dust cleaning on the heat-treated carrier;

[0053] Performance testing unit, used to test the performance of the catalyst obtained after post-treatment, including specific surface area, porosity, active component dispersion and catalytic activity evaluation;

[0054] Aging unit, used to age the catalyst under conditions simulating actual operating conditions to evaluate its long-term stability and durability;

[0055] The encapsulation unit is used to encapsulate the catalyst that has undergone performance testing and aging treatment. The advantages of the present invention are:

[0056] Raw material diversity: A variety of raw materials are mixed to form a composite carrier, which increases the active sites and stability of the catalyst.

[0057] Simplified preparation process: The entire preparation process has clear steps, simple operation, and is easy to implement industrial production.

[0058] High specific surface area: By precisely controlling the drying and calcination steps, catalysts with high specific surface area can be obtained, providing more active sites.

[0059] Uniform distribution of active components: The secondary calcination and impregnation steps ensure uniform distribution of active components on the support, improving the efficiency and stability of the catalyst.

[0060] Enhanced Adhesion: Cleaning and pickling in the pretreatment step help remove impurities and enhance adhesion between the active components and the support.

[0061] Precise impregnation control: By controlling the concentration and time of the impregnation solution, the loading amount of active components can be precisely controlled to optimize the performance of the catalyst.

[0062] Thermal treatment optimization: The thermal treatment step performed in an inert gas atmosphere helps to reduce the sintering of active components and maintain high dispersion of the catalyst.

[0063] Comprehensive post-processing: Post-processing steps including cutting, grinding and cleaning ensure the final morphology and surface quality of the catalyst.

[0064] Strict performance testing: The high performance of the catalyst is ensured through performance tests such as specific surface area, porosity, active component dispersion and catalytic activity evaluation.

[0065] Long-term stability evaluation: The aging treatment step simulates actual operating conditions to evaluate the long-term stability and durability of the catalyst, ensuring its reliability in actual applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 It is a main structural block diagram of the device of the present invention. DETAILED DESCRIPTION

[0067] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, these embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.

[0068] Example 1: A method for preparing a honeycomb CO oxidation catalyst with a simplified process, comprising the following steps:

[0069] (1) Raw material mixing: TiO2, CeO2, ZrO2, Fe2O3, Nb2O5, CaO and SiO2 are weighed according to the ratio and mixed with deionized water to form the basic composition of the catalyst;

[0070] The step (1) is specifically as follows: the weight parts of the components of the raw materials are as follows: 60 parts of TiO2; 15 parts of CeO2; 5 parts of ZrO2; 5 parts of Fe2O3; 6 parts of Nb2O5; 5 parts of SiO2; 1 part of CaO, wherein the total amount of deionized water is 30% of the total weight of the raw materials.

[0071] (2) Preparation of sol: mixing the basic component with the stabilizer to form a uniform sol; the step (2) is specifically as follows: the stabilizer is polyvinyl alcohol to prevent the particles in the sol from agglomerating and maintain the uniformity of the sol; the mass ratio of the stabilizer to the basic component is 1:0.1.

[0072] (3) Gelation: Aging the sol to form a gel; in the step (3), the aging temperature of the sol is controlled at 20° C. and the aging time is 2 hours.

[0073] (4) Drying: Drying the gel at 60°C to form a xerogel;

[0074] (5) Initial calcination: calcining the dry gel at 500 °C to form a preliminary catalyst structure;

[0075] (6) Pretreatment: The catalyst structure after the initial calcination is pretreated to form a carrier, and the pretreatment includes washing and acid washing steps to enhance the adhesion of the active components;

[0076] (7) Secondary calcination: The pretreated support is subjected to secondary calcination to ensure the cleanliness of the support surface and the uniform distribution of the active components;

[0077] (8) Impregnation: The secondary calcined support is impregnated in an impregnation solution, wherein the concentration of the impregnation solution is controlled at 0.5 wt % and the impregnation time is controlled at 0.5 h;

[0078] The impregnation liquid is a metal salt solution (such as nitrate, chloride, etc.), nitrates such as platinum nitrate, palladium nitrate, copper nitrate, etc., these nitrates are usually dissolved in water to form a transparent or slightly transparent solution. Chlorides: such as ruthenium chloride, rhodium chloride, etc., these chlorides have good solubility in organic solvents.

[0079] It can also be a metal organic complex solution, such as a metal chelate: for example, ferrocene and cobaltocene.

[0080] (9) Heat treatment: The impregnated support is heat treated in an inert gas atmosphere at a temperature of 200° C. for 2 hours.

[0081] (10) Post-processing: cutting, grinding and cleaning the heat-treated carrier;

[0082] (11) Performance testing: The catalyst obtained by post-treatment is subjected to performance testing, including specific surface area, porosity, dispersion of active components and catalytic activity evaluation;

[0083] (12) Aging treatment: The catalyst is aged under conditions simulating actual operating conditions to evaluate its long-term stability and durability;

[0084] (13) Packaging: Packaging the catalyst that has undergone performance testing and aging treatment;

[0085] In the step (6), the pickling step is specifically as follows:

[0086] Select dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid as the pickling solution, and the concentration of the pickling solution is 8%; the temperature of the pickling process is controlled at room temperature to ensure the pickling effect and reduce corrosion to the catalyst; the pickling time is usually 30 minutes; after pickling, the catalyst is rinsed with deionized water to neutralize the residual acid solution and ensure that the catalyst surface reaches neutrality; in the step (7), the temperature range of the secondary calcination is between 400°C and 800°C, and the calcination time is 3 hours.

[0087] The step (11) is specifically as follows:

[0088] First, the catalyst samples were degassed to remove the gas adsorbed on the surface;

[0089] Then, the sample was cooled to liquid nitrogen temperature, nitrogen was gradually injected into the sample, and the adsorption amount was measured;

[0090] The specific surface area A was calculated using the BET equation:

[0091] Among them, V 吸附 The adsorption volume is 0.5 cm 3 / g,N A is Avogadro's constant (6.022 x 10 2 3 / mol, R is the gas constant of 8.314 J / (mol·K), P0 is the saturated vapor pressure of 1 atm, C is the adsorbate-adsorbent interaction constant of 100, P is the equilibrium pressure of 0.1 atm, and θ is the coverage of the adsorbed gas of 0.4;

[0092] The pore volume and pore size distribution were determined by nitrogen adsorption method and calculated by the following formula: V 孔 is the pore volume, which is 0.3 cm 3 / g,V 催化剂 is the total volume of the catalyst, 1 cm 3 ;

[0093] Active component dispersion test: X-ray diffraction and transmission electron microscopy were used to observe the crystal structure of the catalyst and the distribution of active components;

[0094] The metal dispersion D is calculated by the following formula:

[0095] Among them, A 金属 is the surface area of ​​the metal component, assumed to be 80m 2 / g,A 总 is the total surface area of ​​the catalyst, assumed to be 120 m 2 / g;

[0096] The catalytic activity was evaluated by the turnover frequency:

[0097] Conversion frequency = reaction rate / number of active sites, where the reaction rate is expressed in moles per second, assuming 0.01 mol / s, and the number of active sites is determined by X-ray photoelectron spectroscopy, assuming 1x 10 2 °sites / g.

[0098] The step (12) is specifically as follows:

[0099] Aging condition setting: Set the temperature, humidity and gas flow parameters for aging treatment; the temperature is set to 500°C, the humidity is 10%, and the gas flow is 2L / min;

[0100] Temperature Control: Use the PID control algorithm to accurately control the temperature of the aging process. The output of the PID controller can be calculated by the following formula:

[0101] Kp is the proportional gain, Ki is the integral gain, K d is the differential gain, e(t) is the deviation, i.e. the difference between the desired temperature and the actual temperature, and dt is the time interval;

[0102] Humidity control: The humidity in the aging environment is controlled by adjusting the flow and concentration of water vapor. Humidity control is monitored and adjusted by the following formula:

[0103] H = W / P × 100% where W is the partial pressure of water vapor and P is the saturated partial pressure of water vapor;

[0104] Gas flow control: Use a mass flow controller to control the gas flow. The gas flow Q is calculated by the following formula: Q = V / t, where V is volume and t is time;

[0105] Aging time: The aging time is estimated by the following formula: T = T0 × e (-k·ΔH) ; Where T0 is the initial time, k is the rate constant 0.01 / h, and ΔH is the activation energy of the aging reaction, which is 40kJ / mol.

[0106] The present invention also relates to a device for implementing the method for preparing the honeycomb CO oxidation catalyst with simplified process, comprising:

[0107] A raw material mixing unit 1, used for mixing raw materials;

[0108] The sol preparation unit 2 is used to mix the basic composition with the stabilizer to form a uniform sol;

[0109] A gel forming unit 3, used for aging the sol to form a gel;

[0110] A drying unit 4, used for drying the gel to form a xerogel;

[0111] A primary calcination unit 5 is used to calcine the dry gel to form a preliminary catalyst structure;

[0112] A pretreatment unit 6 is used to pretreat the catalyst structure after the primary calcination to form a carrier;

[0113] A secondary calcination unit 7, used for secondary calcining the pretreated carrier;

[0114] An impregnation unit 8, used to immerse the secondary calcined support in an impregnation liquid;

[0115] The heat treatment unit 9 is used to heat treat the impregnated carrier in an inert gas atmosphere; the post-treatment unit 10 is used to perform post-treatment steps of cutting, grinding and dust cleaning on the heat-treated carrier;

[0116] The performance testing unit 11 is used to perform performance testing on the catalyst obtained by post-treatment, including specific surface area, porosity, active component dispersion and catalytic activity evaluation;

[0117] An aging treatment unit 12 is used to perform aging treatment on the catalyst under conditions simulating actual working conditions to evaluate its long-term stability and durability;

[0118] The packaging unit 13 is used to package the catalyst that has undergone performance testing and aging treatment.

[0119] Embodiment 2:

[0120] A preparation method of a honeycomb CO oxidation catalyst with a simplified process comprises the following steps:

[0121] (1) Mixing raw materials: weigh TiO2, CeO2, ZrO2, Fe2O3, Nb2O5, CaO and SiO2 raw materials according to the proportions, and mix them with deionized water to form the basic components of the catalyst; the step (1) is specifically that the weight parts of the components of the raw materials are as follows: 65 parts of TiO2; 20 parts of CeO2; 8 parts of ZrO2; 8 parts of Fe2O3; 3 parts of Nb2O5; 8 parts of SiO2; 2 parts of CaO, wherein the total amount of deionized water is 35% of the total weight of the raw materials.

[0122] (2) Sol preparation: mixing the base composition with the stabilizer to form a uniform sol;

[0123] (3) Gelation: Aging the sol to form a gel;

[0124] (4) Drying: Drying the gel at 70°C to form a xerogel;

[0125] (5) Initial calcination: calcining the dry gel at 600 °C to form a preliminary catalyst structure;

[0126] (6) Pretreatment: The catalyst structure after the initial calcination is pretreated to form a carrier, and the pretreatment includes washing and acid washing steps to enhance the adhesion of the active components;

[0127] (7) Secondary calcination: The pretreated support is subjected to secondary calcination to ensure the cleanliness of the support surface and the uniform distribution of the active components;

[0128] (8) Impregnation: The secondary calcined support is impregnated in an impregnation solution, the concentration of the impregnation solution is controlled at 5 wt % and the impregnation time is controlled at 1 hour;

[0129] (9) Heat treatment: The impregnated support is heat treated in an inert gas atmosphere at a temperature of 300° C. for 5 hours.

[0130] (10) Post-processing: cutting, grinding and cleaning the heat-treated carrier;

[0131] (11) Performance testing: The catalyst obtained by post-treatment is subjected to performance testing, including specific surface area, porosity, dispersion of active components and catalytic activity evaluation;

[0132] (12) Aging treatment: The catalyst is aged under conditions simulating actual operating conditions to evaluate its long-term stability and durability;

[0133] (13) Packaging: Packaging the catalyst that has undergone performance testing and aging treatment;

[0134] The step (2) is specifically as follows: the stabilizer is polyacrylic acid, so as to prevent the particles in the sol from agglomerating and maintain the uniformity of the sol; the mass ratio of the stabilizer to the basic component is 1:0.2.

[0135] In the step (3), the sol aging temperature is controlled at 30° C. and the aging time is 5 hours.

[0136] In the step (6), the pickling step is specifically as follows:

[0137] Select dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid as the pickling solution, and the concentration of the pickling solution is 5%; the temperature of the pickling process is controlled at 30°C to ensure the pickling effect and reduce corrosion to the catalyst; the pickling time is usually 1 hour; after pickling, use deionized water to rinse the catalyst to neutralize the residual acid solution and ensure that the catalyst surface reaches neutrality; in the step (7), the temperature of the secondary calcination is 500°C and the calcination time is 5 hours.

[0138] The step (11) is specifically as follows:

[0139] First, the catalyst samples were degassed to remove the gas adsorbed on the surface;

[0140] Then, the sample was cooled to liquid nitrogen temperature, nitrogen was gradually injected into the sample, and the adsorption amount was measured;

[0141] The specific surface area A was calculated using the BET equation:

[0142] The pore volume and pore size distribution were determined by nitrogen adsorption method and calculated by the following formula: V 孔 is the pore volume, V 催化剂 is the total volume of the catalyst;

[0143] Active component dispersion test: X-ray diffraction and transmission electron microscopy were used to observe the crystal structure of the catalyst and the distribution of active components;

[0144] The metal dispersion D is calculated by the following formula:

[0145] Among them, A 金属 is the surface area of ​​the metal component, A 总 is the total surface area of ​​the catalyst;

[0146] The catalytic activity was evaluated by the turnover frequency:

[0147] Conversion frequency = reaction rate / number of active sites, where the reaction rate is expressed in moles per second and the number of active sites is determined by X-ray photoelectron spectroscopy.

[0148] The step (12) is specifically as follows:

[0149] Aging condition setting: set the temperature, humidity and gas flow parameters for aging treatment;

[0150] Temperature Control: Use the PID control algorithm to accurately control the temperature of the aging process. The output of the PID controller can be calculated by the following formula:

[0151] Kp is the proportional gain, Ki is the integral gain, K d is the differential gain, e(t) is the deviation, i.e. the difference between the desired temperature and the actual temperature, and dt is the time interval;

[0152] Humidity control: The humidity in the aging environment is controlled by adjusting the flow and concentration of water vapor. Humidity control is monitored and adjusted by the following formula:

[0153] H = W / P × 100% where W is the partial pressure of water vapor and P is the saturated partial pressure of water vapor;

[0154] Gas flow control: Use a mass flow controller to control the gas flow. The gas flow Q is calculated by the following formula: Q = V / t, where V is volume and t is time;

[0155] Aging time: The aging time is estimated by the following formula: T = T0 × e (-k·ΔH) ; Where T0 is the initial time, k is the rate constant, and ΔH is the activation energy of the aging reaction.

[0156] Embodiment 3:

[0157] A preparation method of a honeycomb CO oxidation catalyst with a simplified process comprises the following steps:

[0158] (1) Raw material mixing: TiO2, CeO2, ZrO2, Fe2O3, Nb2O5, CaO and SiO2 are weighed according to the ratio and mixed with deionized water to form the basic composition of the catalyst;

[0159] (2) Sol preparation: mixing the base composition with the stabilizer to form a uniform sol;

[0160] (3) Gelation: Aging the sol to form a gel;

[0161] (4) Drying: Drying the gel at 75°C to form a xerogel;

[0162] (5) Initial calcination: calcining the dry gel at 800 °C to form a preliminary catalyst structure;

[0163] (6) Pretreatment: The catalyst structure after the initial calcination is pretreated to form a carrier, and the pretreatment includes washing and acid washing steps to enhance the adhesion of the active components;

[0164] (7) Secondary calcination: The pretreated support is subjected to secondary calcination to ensure the cleanliness of the support surface and the uniform distribution of the active components;

[0165] (8) Impregnation: The secondary calcined support is impregnated in an impregnation solution, the concentration of the impregnation solution is controlled at 10 wt % and the impregnation time is controlled at 2 hours;

[0166] (9) Heat treatment: The impregnated support is heat treated in an inert gas atmosphere at a temperature of 500° C. for 12 hours;

[0167] (10) Post-processing: cutting, grinding and cleaning the heat-treated carrier;

[0168] (11) Performance testing: The catalyst obtained by post-treatment is subjected to performance testing, including specific surface area, porosity, dispersion of active components and catalytic activity evaluation;

[0169] (12) Aging treatment: The catalyst is aged under conditions simulating actual operating conditions to evaluate its long-term stability and durability;

[0170] (13) Packaging: Packaging the catalyst that has undergone performance testing and aging treatment;

[0171] The step (1) is specifically as follows: the weight parts of the components of the raw materials are as follows: 75 parts of TiO2; 25 parts of CeO2; 10 parts of ZrO2; 10 parts of Fe2O3; 55 parts of Nb2O5; 10 parts of SiO2; 3 parts of CaO, wherein the total amount of deionized water is 40% of the total weight of the raw materials.

[0172] The step (2) is specifically as follows: the stabilizer is polyvinyl alcohol or polyacrylic acid to prevent the particles in the sol from agglomerating and maintain the uniformity of the sol; the mass ratio of the stabilizer to the basic component is 1:0.5.

[0173] In the step (3), the sol aging temperature is controlled at 40° C. and the aging time is 24 hours.

[0174] In the step (6), the pickling step is specifically as follows:

[0175] Select dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid as the pickling solution, the concentration of the pickling solution is 10%; the temperature of the pickling process is controlled at 60°C to ensure the pickling effect and reduce corrosion to the catalyst; the pickling time is 2 hours; after pickling, use deionized water to rinse the catalyst to neutralize the residual acid solution and ensure that the catalyst surface reaches neutrality; in the step (7), the temperature of the secondary calcination is 800°C and the calcination time is 15 hours.

[0176] The step (11) is specifically as follows:

[0177] First, the catalyst samples were degassed to remove the gas adsorbed on the surface;

[0178] Then, the sample was cooled to liquid nitrogen temperature, nitrogen was gradually injected into the sample, and the adsorption amount was measured;

[0179] The specific surface area A was calculated using the BET equation:

[0180] Where Vadsorption Vadsorption is the adsorption volume (assumed to be 0.5 cm 3 / g), NANA is Avogadro's constant (6.022x 10 23 mol -1 ), RR is the gas constant (8.314 J / (mol·K)), P0P0 is the saturated vapor pressure (assumed to be 1 atm), CC is the adsorbate-adsorbent interaction constant (assumed to be 100), PP is the equilibrium pressure (assumed to be 0.1 atm), and θθ is the coverage of the adsorbed gas (assumed to be 0.4). ;

[0181] The pore volume and pore size distribution were determined by nitrogen adsorption method and calculated by the following formula: V 孔 is the pore volume, V 催化剂 is the total volume of the catalyst;

[0182] Active component dispersion test: X-ray diffraction and transmission electron microscopy were used to observe the crystal structure of the catalyst and the distribution of active components;

[0183] The metal dispersion D is calculated by the following formula:

[0184] Among them, A 金属 is the surface area of ​​the metal component, A 总 is the total surface area of ​​the catalyst;

[0185] The catalytic activity was evaluated by the turnover frequency:

[0186] Conversion frequency = reaction rate / number of active sites, where the reaction rate is expressed in moles per second and the number of active sites is determined by X-ray photoelectron spectroscopy.

[0187] The step (12) is specifically as follows:

[0188] Aging condition setting: set the temperature, humidity and gas flow parameters for aging treatment;

[0189] Temperature Control: Use the PID control algorithm to accurately control the temperature of the aging process. The output of the PID controller can be calculated by the following formula:

[0190] Kp is the proportional gain, Ki is the integral gain, K d is the differential gain, e(t) is the deviation, i.e. the difference between the desired temperature and the actual temperature, and dt is the time interval;

[0191] Humidity control: The humidity in the aging environment is controlled by adjusting the flow and concentration of water vapor. Humidity control is monitored and adjusted by the following formula:

[0192] H = W / P × 100% where W is the partial pressure of water vapor and P is the saturated partial pressure of water vapor;

[0193] Gas flow control: Use a mass flow controller to control the gas flow. The gas flow Q is calculated by the following formula: Q = V / t, where V is volume and t is time;

[0194] Aging time: The aging time is estimated by the following formula: T = T0 × e (-k·ΔH) ; Where T0 is the initial time, k is the rate constant, and ΔH is the activation energy of the aging reaction.

[0195] Embodiment 4:

[0196] A preparation method of a honeycomb CO oxidation catalyst with a simplified process comprises the following steps:

[0197] (1) Raw material mixing: TiO2, CeO2, ZrO2, Fe2O3, Nb2O5, CaO and SiO2 are weighed according to the ratio and mixed with deionized water to form the basic composition of the catalyst;

[0198] (2) Sol preparation: mixing the base composition with the stabilizer to form a uniform sol;

[0199] (3) Gelation: Aging the sol to form a gel;

[0200] (4) Drying: Drying the gel at 75°C to form a xerogel;

[0201] (5) Initial calcination: calcining the dry gel at 700 °C to form a preliminary catalyst structure;

[0202] (6) Pretreatment: The catalyst structure after the initial calcination is pretreated to form a carrier, and the pretreatment includes washing and acid washing steps to enhance the adhesion of the active components;

[0203] (7) Secondary calcination: The pretreated support is subjected to secondary calcination to ensure the cleanliness of the support surface and the uniform distribution of the active components;

[0204] (8) Impregnation: The secondary calcined support is impregnated in an impregnation solution, wherein the concentration of the impregnation solution is controlled at 8 wt % and the impregnation time is controlled at 1.5 hours;

[0205] (9) Heat treatment: The impregnated support is heat treated in an inert gas atmosphere at a temperature of 400° C. for 11 hours.

[0206] (10) Post-processing: cutting, grinding and cleaning the heat-treated carrier;

[0207] (11) Performance testing: The catalyst obtained by post-treatment is subjected to performance testing, including specific surface area, porosity, dispersion of active components and catalytic activity evaluation;

[0208] (12) Aging treatment: The catalyst is aged under conditions simulating actual operating conditions to evaluate its long-term stability and durability;

[0209] (13) Packaging: Packaging the catalyst that has undergone performance testing and aging treatment;

[0210] The step (1) is specifically as follows: the weight parts of the components of the raw materials are as follows: 72 parts of TiO2; 23 parts of CeO2; 9 parts of ZrO2; 9 parts of Fe2O3; 55 parts of Nb2O; 9 parts of SiO2; 2 parts of CaO, wherein the total amount of deionized water is 35% of the total weight of the raw materials.

[0211] The step (2) is specifically as follows: the stabilizer is polyvinyl alcohol or polyacrylic acid to prevent the particles in the sol from agglomerating and maintain the uniformity of the sol; the mass ratio of the stabilizer to the basic component is 1:0.4.

[0212] In the step (3), the sol aging temperature is controlled at 35° C. and the aging time is 20 hours.

[0213] In the step (6), the pickling step is specifically as follows:

[0214] Select dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid as the pickling solution, and the concentration of the pickling solution is 6%; the temperature of the pickling process is controlled between room temperature and 60°C to ensure the pickling effect and reduce corrosion to the catalyst; the pickling time is 1.5 hours; after pickling, the catalyst is rinsed with deionized water to neutralize the residual acid solution and ensure that the catalyst surface reaches neutrality; in the step (7), the secondary calcination range is 700°C and the calcination time is 11 hours.

[0215] The step (11) is specifically as follows:

[0216] First, the catalyst samples were degassed to remove the gas adsorbed on the surface;

[0217] Then, the sample was cooled to liquid nitrogen temperature, nitrogen was gradually injected into the sample, and the adsorption amount was measured;

[0218] The specific surface area A was calculated using the BET equation:

[0219] Where Vadsorption Vadsorption is the adsorption volume (assumed to be 0.5 cm 3 / g), NANA is Avogadro's constant (6.022x 10 23 mol -1 ), RR is the gas constant (8.314 J / (mol·K)), P0P0 is the saturated vapor pressure (assumed to be 1 atm), CC is the adsorbate-adsorbent interaction constant (assumed to be 100), PP is the equilibrium pressure (assumed to be 0.1 atm), and θθ is the coverage of the adsorbed gas (assumed to be 0.4). ;

[0220] The pore volume and pore size distribution were determined by nitrogen adsorption method and calculated by the following formula: V 孔 is the pore volume, V 催化剂 is the total volume of the catalyst;

[0221] Active component dispersion test: X-ray diffraction and transmission electron microscopy were used to observe the crystal structure of the catalyst and the distribution of active components;

[0222] The metal dispersion D is calculated by the following formula:

[0223] Among them, A 金属is the surface area of ​​the metal component, A 总 is the total surface area of ​​the catalyst;

[0224] The catalytic activity was evaluated by the turnover frequency:

[0225] Conversion frequency = reaction rate / number of active sites, where the reaction rate is expressed in moles per second and the number of active sites is determined by X-ray photoelectron spectroscopy.

[0226] The step (12) is specifically as follows:

[0227] Aging condition setting: set the temperature, humidity and gas flow parameters for aging treatment;

[0228] Temperature Control: Use the PID control algorithm to accurately control the temperature of the aging process. The output of the PID controller can be calculated by the following formula:

[0229] Kp is the proportional gain, Ki is the integral gain, K d is the differential gain, e(t) is the deviation, i.e. the difference between the desired temperature and the actual temperature, and dt is the time interval;

[0230] Humidity control: The humidity in the aging environment is controlled by adjusting the flow and concentration of water vapor. Humidity control is monitored and adjusted by the following formula:

[0231] H = W / P × 100% where W is the partial pressure of water vapor and P is the saturated partial pressure of water vapor;

[0232] Gas flow control: Use a mass flow controller to control the gas flow. The gas flow Q is calculated by the following formula: Q = V / t, where V is volume and t is time;

[0233] Aging time: The aging time is estimated by the following formula: T = T0 × e (-k·ΔH) ; Where T0 is the initial time, k is the rate constant, and ΔH is the activation energy of the aging reaction.

[0234] Embodiment 5:

[0235] A preparation method of a honeycomb CO oxidation catalyst with a simplified process comprises the following steps:

[0236] (1) Raw material mixing: TiO2, CeO2, ZrO2, Fe2O3, Nb2O5, CaO and SiO2 are weighed according to the ratio and mixed with deionized water to form the basic composition of the catalyst;

[0237] (2) Sol preparation: mixing the base composition with the stabilizer to form a uniform sol;

[0238] (3) Gelation: Aging the sol to form a gel;

[0239] (4) Drying: Drying the gel at 77°C to form a xerogel;

[0240] (5) Initial calcination: calcining the dry gel at 780 °C to form a preliminary catalyst structure;

[0241] (6) Pretreatment: The catalyst structure after the initial calcination is pretreated to form a carrier, and the pretreatment includes washing and acid washing steps to enhance the adhesion of the active components;

[0242] (7) Secondary calcination: The pretreated support is subjected to secondary calcination to ensure the cleanliness of the support surface and the uniform distribution of the active components;

[0243] (8) Impregnation: The secondary calcined support is impregnated in an impregnation solution, wherein the concentration of the impregnation solution is controlled at 6 wt % and the impregnation time is controlled at 0.8 h;

[0244] (9) Heat treatment: The impregnated support is heat treated in an inert gas atmosphere at a temperature of 450° C. for 11 hours.

[0245] (10) Post-processing: cutting, grinding and cleaning the heat-treated carrier;

[0246] (11) Performance testing: The catalyst obtained by post-treatment is subjected to performance testing, including specific surface area, porosity, dispersion of active components and catalytic activity evaluation;

[0247] (12) Aging treatment: The catalyst is aged under conditions simulating actual operating conditions to evaluate its long-term stability and durability;

[0248] (13) Packaging: Packaging the catalyst that has undergone performance testing and aging treatment;

[0249] The step (1) is specifically as follows: the weight parts of the components of the raw materials are as follows: TiO2 60-75 parts; CeO2 23 parts; ZrO2 8 parts; Fe2O3 9 parts; Nb2O5 4 parts; SiO2 9 parts; CaO 2 parts, wherein the total amount of deionized water is 39% of the total weight of the raw materials.

[0250] The step (2) is specifically as follows: the stabilizer is polyvinyl alcohol or polyacrylic acid to prevent the particles in the sol from agglomerating and maintain the uniformity of the sol; the mass ratio of the stabilizer to the basic component is 1:0.5.

[0251] In the step (3), the sol aging temperature is controlled at 38° C. and the aging time is 23 hours.

[0252] In the step (6), the pickling step is specifically as follows:

[0253] Select dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid as the pickling solution, and the concentration of the pickling solution is 10%; the temperature of the pickling process is controlled at 55°C to ensure the pickling effect and reduce corrosion to the catalyst; the pickling time is 2 hours; after pickling, the catalyst is rinsed with deionized water to neutralize the residual acid solution and ensure that the catalyst surface reaches neutrality; in the step (7), the temperature of the secondary calcination is 800°C and the calcination time is 14 hours.

[0254] The step (11) is specifically as follows:

[0255] First, the catalyst samples were degassed to remove the gas adsorbed on the surface;

[0256] Then, the sample was cooled to liquid nitrogen temperature, nitrogen was gradually injected into the sample, and the adsorption amount was measured;

[0257] The specific surface area A was calculated using the BET equation:

[0258] Where Vadsorption Vadsorption is the adsorption volume (assumed to be 0.5 cm 3 / g), NANA is Avogadro's constant (6.022x 10 23 mol -1 ), RR is the gas constant (8.314 J / (mol·K)), P0P0 is the saturated vapor pressure (assumed to be 1 atm), CC is the adsorbate-adsorbent interaction constant (assumed to be 100), PP is the equilibrium pressure (assumed to be 0.1 atm), and θθ is the coverage of the adsorbed gas (assumed to be 0.4). ;

[0259] The pore volume and pore size distribution were determined by nitrogen adsorption method and calculated by the following formula: V 孔 is the pore volume, V 催化剂 is the total volume of the catalyst;

[0260] Active component dispersion test: X-ray diffraction and transmission electron microscopy were used to observe the crystal structure of the catalyst and the distribution of active components;

[0261] The metal dispersion D is calculated by the following formula:

[0262] Among them, A 金属 is the surface area of ​​the metal component, A 总 is the total surface area of ​​the catalyst;

[0263] The catalytic activity was evaluated by the turnover frequency:

[0264] Conversion frequency = reaction rate / number of active sites, where the reaction rate is expressed in moles per second and the number of active sites is determined by X-ray photoelectron spectroscopy.

[0265] The step (12) is specifically as follows:

[0266] Aging condition setting: set the temperature, humidity and gas flow parameters for aging treatment;

[0267] Temperature Control: Use the PID control algorithm to accurately control the temperature of the aging process. The output of the PID controller can be calculated by the following formula:

[0268] Kp is the proportional gain, Ki is the integral gain, K d is the differential gain, e(t) is the deviation, i.e. the difference between the desired temperature and the actual temperature, and dt is the time interval;

[0269] Humidity control: The humidity in the aging environment is controlled by adjusting the flow and concentration of water vapor. Humidity control is monitored and adjusted by the following formula:

[0270] H = W / P × 100% where W is the partial pressure of water vapor and P is the saturated partial pressure of water vapor;

[0271] Gas flow control: Use a mass flow controller to control the gas flow. The gas flow Q is calculated by the following formula: Q = V / t, where V is volume and t is time;

[0272] Aging time: The aging time is estimated by the following formula: T = T0 × e (-k·ΔH) ; Wherein, T0 is the initial time, k is the rate constant, and ΔH is the activation energy of the aging reaction. The effects produced by the embodiments of the present invention are as follows:

[0273]

[0274] Technical effect: By comparing the experimental data of the five examples, it can be observed that the increase in specific surface area, porosity and active component dispersion is correlated with the improvement of catalytic activity. In particular, Example 5 has a higher specific surface area and porosity, a higher active component dispersion, and exhibits the best catalytic activity, with a CO conversion rate of 75%. This shows that by optimizing the physical properties of the catalyst, its catalytic performance can be significantly improved.

[0275] In addition, the data of Examples 2 and 4 show that even when the dispersion of the active components is low, higher catalytic activity can be obtained by increasing the specific surface area and porosity. This emphasizes that in catalyst design, not only the dispersion of the active components but also the overall physical structure of the catalyst should be considered.

[0276] In summary, the technical solution achieves a catalyst with high specific surface area, high porosity and high active component dispersion by precisely controlling the preparation parameters of the catalyst, thereby providing excellent CO oxidation performance. In practical applications, these catalysts can more effectively convert CO and reduce harmful gas emissions, and have important application value for environmental protection and industrial catalytic processes.

[0277] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a honeycomb CO oxidation catalyst with a simplified process, characterized in that: The following steps are involved: (1) Raw material mixing: TiO2, CeO2, ZrO2, Fe2O3, Nb2O5, CaO and SiO2 are weighed according to the ratio and mixed with deionized water to form the basic composition of the catalyst; (2) Sol preparation: mixing the base composition with the stabilizer to form a uniform sol; (3) Gelation: Aging the sol to form a gel; (4) Drying: Drying the gel at 60-80°C to form a xerogel; (5) Initial calcination: calcining the dry gel at 500-800 °C to form a preliminary catalyst structure; (6) Pretreatment: The catalyst structure after the initial calcination is pretreated to form a carrier, and the pretreatment includes washing and acid washing steps to enhance the adhesion of the active components; (7) Secondary calcination: The pretreated support is subjected to secondary calcination to ensure the cleanliness of the support surface and the uniform distribution of the active components; (8) Impregnation: Impregnating the secondary calcined support in an impregnation solution, wherein the concentration of the impregnation solution is controlled at 0.5 to 10 wt % and the impregnation time is controlled at 0.5 to 2 h; (9) Heat treatment: The impregnated support is heat treated in an inert gas atmosphere at a temperature of 200-500° C. for a time of 2-12 hours; (10) Post-processing: cutting, grinding and cleaning the heat-treated carrier; (11) Performance testing: The catalyst obtained by post-treatment is subjected to performance testing, including specific surface area, porosity, dispersion of active components and catalytic activity evaluation; (12) Aging treatment: The catalyst is aged under conditions simulating actual operating conditions to evaluate its long-term stability and durability; (13) Packaging: The catalyst that has undergone performance testing and aging treatment is packaged.

2. The method for preparing a honeycomb CO oxidation catalyst with a simplified process according to claim 1, characterized in that: The step (1) is specifically as follows: the weight parts of the components of the raw materials are as follows: TiO2 60-75 parts; CeO2 15-25 parts; ZrO2 5-10 parts; Fe2O3 5-10 parts; Nb2O5 3-6 parts; SiO2 5-10 parts; CaO 1-3 parts, wherein the total amount of deionized water is 30% to 40% of the total weight of the raw materials.

3. The method for preparing a honeycomb CO oxidation catalyst with a simplified process according to claim 1, characterized in that: The step (2) is specifically as follows: the stabilizer is polyvinyl alcohol or polyacrylic acid to prevent the particles in the sol from agglomerating and maintain the uniformity of the sol; the mass ratio of the stabilizer to the basic component is 1:0.1-1:0.

5.

4. The method for preparing a honeycomb CO oxidation catalyst with a simplified process according to claim 1, characterized in that: In the step (3), the sol aging temperature is controlled at 20-40° C., and the aging time is 2-24 hours.

5. The method for preparing a honeycomb CO oxidation catalyst with a simplified process according to claim 1, characterized in that: In the step (6), the pickling step is specifically as follows: Select dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid as the pickling solution, and the concentration of the pickling solution is between 1% and 10%; the temperature of the pickling process is controlled between room temperature and 60°C to ensure the pickling effect and reduce corrosion to the catalyst; the pickling time is usually 30 minutes to 2 hours; after pickling, use deionized water to rinse the catalyst to neutralize the residual acid solution and ensure that the catalyst surface reaches neutrality; in the step (7), the temperature range of the secondary calcination is between 400°C and 800°C, and the calcination time is 3-15 hours.

6. The method for preparing a honeycomb CO oxidation catalyst with a simplified process according to claim 1 or 2, characterized in that: The step (11) is specifically as follows: First, the catalyst samples were degassed to remove the gases adsorbed on the surface; Then, the sample was cooled to liquid nitrogen temperature, nitrogen was gradually injected into the sample, and the adsorption amount was measured; The specific surface area A was calculated using the BET equation: Among them, V 吸附 is the adsorption volume, NA is Avogadro's constant, R is the gas constant, P0 is the saturated vapor pressure, C is the adsorbate-adsorbent interaction constant, P is the equilibrium pressure, and θ is the coverage of the adsorbed gas; The pore volume and pore size distribution were determined by nitrogen adsorption method and calculated by the following formula: V 孔 is the pore volume, V 催化剂 is the total volume of the catalyst; Active component dispersion test: X-ray diffraction and transmission electron microscopy were used to observe the crystal structure of the catalyst and the distribution of active components; The metal dispersion D is calculated by the following formula: Among them, A 金属 is the surface area of ​​the metal component, A 总 is the total surface area of ​​the catalyst; The catalytic activity was evaluated by the turnover frequency: Conversion frequency = reaction rate / number of active sites, where the reaction rate is expressed in moles per second and the number of active sites is determined by X-ray photoelectron spectroscopy.

7. The method for preparing a honeycomb CO oxidation catalyst with a simplified process according to claim 1 or 2, characterized in that: The step (12) is specifically as follows: Aging condition setting: set the temperature, humidity and gas flow parameters for aging treatment; Temperature Control: Use the PID control algorithm to accurately control the temperature of the aging process. The output of the PID controller can be calculated by the following formula: Kp is the proportional gain, Ki is the integral gain, K d is the differential gain, e(t) is the deviation, i.e. the difference between the desired temperature and the actual temperature, and dt is the time interval; Humidity control: The humidity in the aging environment is controlled by adjusting the flow and concentration of water vapor. Humidity control is monitored and adjusted by the following formula: H = W / P × 100% where W is the partial pressure of water vapor and P is the saturated partial pressure of water vapor; Gas flow control: Use a mass flow controller to control the gas flow. The gas flow Q is calculated by the following formula: Q = V / t, where V is volume and t is time; Aging time: The aging time is estimated by the following formula: T = T0 × e (-k·ΔH) ; Where T0 is the initial time, k is the rate constant, and ΔH is the activation energy of the aging reaction.

8. A device for implementing the method for preparing a honeycomb CO oxidation catalyst with a simplified process as described in any one of claims 1 to 7, characterized in that: include: A raw material mixing unit, used for mixing raw materials; A sol preparation unit, used for mixing the basic composition with the stabilizer to form a uniform sol; A gel forming unit, used for aging the sol to form a gel; A drying unit, used for drying the gel to form a xerogel; A primary calcination unit, used to calcine the dry gel to form a preliminary catalyst structure; A pretreatment unit, used to pretreat the catalyst structure after the primary calcination to form a carrier; A secondary calcination unit, used for secondary calcining the pretreated carrier; An impregnation unit, used for impregnating the secondary calcined support into an impregnation liquid; A heat treatment unit, used to heat treat the impregnated carrier in an inert gas atmosphere; A post-processing unit, used for performing post-processing steps of cutting, grinding and dust cleaning on the heat-treated carrier; Performance testing unit, used to test the performance of the catalyst obtained after post-treatment, including specific surface area, porosity, active component dispersion and catalytic activity evaluation; Aging unit, used to age the catalyst under conditions simulating actual operating conditions to evaluate its long-term stability and durability; The packaging unit is used to package the catalyst that has undergone performance testing and aging treatment.